Retskrivningsordbøger- retskrivningsautoriteter - Jacobsen, Henrik Galberg (Nordiske Studier i Leksikografi, 1997)
The subject of this paper is spelling dictionaries in the Nordic countries, primarily the official Danish orthographical dictionary and its Norwegian and Swedish counterparts. In part 2 spelling dictionaries are looked at as a genre, with special reference to the distinction between ’word list’ and ’dictionary’. Part 3 and 4 deal with the spelling dictionary as an authority and discuss the powers of the Scandinavian Language Councils and their influence on the codification of the national orthographical standards. Part 5 focuses on the relations between the official Danish spelling dictionary and other Danish dictionaries intended for school purposes.